Aplicação das normas para adequação de subestação - Simionato, Pâmela Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The first approach in this work is the concept of the electric power transmission and distribution system, as well as the survey of the current condition of substations chosen to thus identify the importance of having a suitable design with respect to security due to the need to obtain the approval for the operation of the substation according to the standards valid in the country. Present the guidelines and present needs when designing improvements, thus ensuring the company for more safety and reliability. From the company's point of view is an opportunity to reduce the cost of maintenance, and the professional point of view is an opportunity that allows a comprehensive study of legal requirements for the operation of substations

Neste trabalho é abordado o conceito de um sistema de transmissão e distribuição de energia elétrica, assim como o levantamento sobre a condição atual das subestações escolhidas para identificar a importância de se ter um projeto adequado com relação a segurança devido a necessidade de se obter o aval para o funcionamento da subestação segundo as normas válidas no país. Apresentar as diretrizes e necessidades presentes na elaboração de melhorias, garantindo assim para à empresa mais segurança e confiabilidade. Do ponto de vista da empresa é uma oportunidade de reduzir os custos com manutenções, e do ponto de vista do profissional é uma oportunidade que permite um estudo amplo das necessidades legislativas para o funcionamento das subestações
Keywords: Energia elétrica - Distribuição; Subestações eletricas; Energia eletrica - Transmissão; Electric power distribution